2020
DOI: 10.3390/ijms22010141
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Microenvironment: Roles of the Aryl Hydrocarbon Receptor, O-GlcNAcylation, Acetyl-CoA and Melatonergic Pathway in Regulating Dynamic Metabolic Interactions across Cell Types—Tumour Microenvironment and Metabolism

Abstract: This article reviews the dynamic interactions of the tumour microenvironment, highlighting the roles of acetyl-CoA and melatonergic pathway regulation in determining the interactions between oxidative phosphorylation (OXPHOS) and glycolysis across the array of cells forming the tumour microenvironment. Many of the factors associated with tumour progression and immune resistance, such as yin yang (YY)1 and glycogen synthase kinase (GSK)3β, regulate acetyl-CoA and the melatonergic pathway, thereby having signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 228 publications
(326 reference statements)
0
24
0
Order By: Relevance
“…Melatonin, to the authors knowledge, is the first endogenously produced molecule that has been shown to be capable of redirecting pyruvate metabolism away from the fermentation pathway and into the mitochondria for the support of the TCA cycle and OXPHOS [23,125]. Thus, the well-documented actions of melatonin on cancer progression [15,17,155,225] may be related to its ability to inhibit elevated cytosolic glycolysis of these cells [226]. Since this may be the case, it is also possible that melatonin's efficiency in reducing the severity of other diseased cells that display this altered metabolism (see Table 1) may likewise be related to its ability to limit pyruvate conversion to lactate and to redirect it into the mitochondria, thereby normalizing the metabolism of this organelle and rendering the cells less-diseased/pathological [20].…”
Section: References Indicating Melatonin Inhibits These Cell Typesmentioning
confidence: 99%
“…Melatonin, to the authors knowledge, is the first endogenously produced molecule that has been shown to be capable of redirecting pyruvate metabolism away from the fermentation pathway and into the mitochondria for the support of the TCA cycle and OXPHOS [23,125]. Thus, the well-documented actions of melatonin on cancer progression [15,17,155,225] may be related to its ability to inhibit elevated cytosolic glycolysis of these cells [226]. Since this may be the case, it is also possible that melatonin's efficiency in reducing the severity of other diseased cells that display this altered metabolism (see Table 1) may likewise be related to its ability to limit pyruvate conversion to lactate and to redirect it into the mitochondria, thereby normalizing the metabolism of this organelle and rendering the cells less-diseased/pathological [20].…”
Section: References Indicating Melatonin Inhibits These Cell Typesmentioning
confidence: 99%
“…Melatonin has been shown to modulate the cargo composition of exosomes and, thereby, the regulatory potential of these vesicles [3,29,220,221]. This was impressively confirmed for MSCs, as recently summarized with a focus on tumor biology [222]. Importantly, MSCs were found to release relatively high amounts of exosomes [223].…”
Section: Msc-derived Exosomes With Protective Anti-inflammatory and A...mentioning
confidence: 79%
“…For instance, overexpressed fatty acyls and glycerophospholipids, such as eicosanoids, lysophosphatidylserine, and phosphatidyl choline, participate in cell signaling of inflammation and immune responses [ 25 , 26 ]. Downregulated metabolites, such as vitamin A [ 27 ] (prenol lipids), N-acetylsphingosine, N-acetylserotonin, and O-arachidonoyl ethanolamine (fatty acyls), could increase the survival likelihood of tumor, proliferation of cancer cells, and immune suppression [ 28 ]. The enriched pathways in both ablation groups, including steroid hormone biosynthesis and tryptophan metabolism, also contributed to tumor progression and immune evasion ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%